Targeted mutagenesis with sequence‐specific nucleases for accelerated improvement of polyploid crops: Progress, challenges, and prospects - David May; Katalin Paldi; Fredy Altpeter (The Plant Genome, 2023)
Abstract Many of the world's most important crops are polyploid. The presence of more than two sets of chromosomes within their nuclei and frequently aberrant reproductive biology in polyploids present obstacles to conventional breeding. The presence of a larger number of homoeologous copies of each gene makes random mutation breeding a daunting task for polyploids. Genome editing has revolutionized improvement of polyploid crops as multiple gene copies and/or alleles can be edited simultaneously while preserving the key attributes of elite cultivars. Most genome‐editing platforms employ sequence‐specific nucleases (SSNs) to generate DNA double‐stranded breaks at their target gene. Such DNA breaks are typically repaired via the error‐prone nonhomologous end‐joining process, which often leads to frame shift mutations, causing loss of gene function. Genome editing has enhanced the disease resistance, yield components, and end‐use quality of polyploid crops. However, identification of candidate targets, genotyping, and requirement of high mutagenesis efficiency remain bottlenecks for targeted mutagenesis in polyploids. In this review, we will survey the tremendous progress of SSN‐mediated targeted mutagenesis in polyploid crop improvement, discuss its challenges, and identify optimizations needed to sustain further progress.